NOTT VA DE-MASSA NAZARIYASIGA ASOSAN TUNNEL DIODINING OʻTISH VAQTINI HISOBLASH - Oʻktamova, M.K.; Mamatshoyev, A.A. (SCIENCE and SOCIETY, 2025)
Based on the Nott and De-Massa theory was calculated, the dependence of the tunnel diode on the diffusion capacitance and the peak current in the tunnel diode. In addition, it was observed that the peak voltage value and the minimum voltage value generated in the tunnel diode also affect the turn-on time of the tunnel diode. The dependence of the tunnel diode was checked on the turn-on time of the tunnel diode on the ratio of the peak current value to the current value at the lowest point in the tunnel diode was obtained theoretically and the degree of agreement with the experimental results.